The cultural value of Adansonia digitata in Sagole community, Limpopo Province, South Africa - Mathaba, M. G.; Rankoana, Sejabaledi Agnes; Potgieter, Martin (Technium Social Sciences Journal, 2021)
Most communities in Africa are transitioning from traditional culture to a western-orientated lifestyle. Traditionally throughout Africa, the baobab (Adansonia digitata) is venerated for its size and longevity, and as such are indelibly embedded in the culture. However, the shift in cultural identity and lifestyle has disconnected numerous communities across Africa from this iconic tree. Thus an investigation was conducted in the Sagole community, Limpopo Province, South Africa to ascertain the level of knowledge of, and cultural value this community still attaches to the baobab. Results indicate that people aged 18-45 are not closely associated with tree species, and lacked significant cultural information. Only the older generation (older than 65 years) still had a strong cultural relationship. Elders from the community are the most knowledgeable with respect to cultural stories, and it is predominantly these elders that inform the younger generations regarding different culturally-bound stories related to the baobab tree. People of Sagole are not fully aware of taboos that relate to the baobab. This disconnect can be traced back to a society in transition from a traditional way of lifestyle to a western-orientated lifestyle, and the consequent uncoupling of generations. Ultimately this will lead to a significant loss of cultural information, cultural identity, the cohesiveness of communities, and environmental degradation in the Sagole community.